MANAGEMENT OF PRODUCTION RISKS IN TECHNOLOGICAL SYSTEMS OF WAGON REPAIR ENTERPRISES (Transport systems and technologies, 2022)
At the moment, the modernization of the wagon repair complex is an urgent scientific and technical task on the railway transport of Ukraine. Wagon repair companies are characterized by insufficient pace of development over time. This is expressed in significant physical and moral depreciation of fixed assets of enterprises, large material losses in the process of repairing wagons, high cost of repair, low mechanization and automation of basic and auxiliary production processes, etc. Bearing in mind that railway transport is a critical component of the transport complex of Ukraine, the creation of advanced production systems based on the principles of production logistics is considered a necessary step for further development of the industry.The presented article analyzes the current state of wagon repair companies. The conclusion is made about the need for risk analysis in production processes given the difficult operating conditions. An example of an algorithm for implementing a risk management system and its main components is given. The analysis of the main methods of influencing the risk in the production system is carried out. Practical solutions for obtaining quantitative indicators of risk assessment in the production processes of wagon repair with the help of Markov analysis are proposed. In general, the risk management system will significantly reduce material losses when repairing wagon.
Keywords: of wagon repair enterprises, production logistics, risk management system, state of the production system.